Døden i livet - Johannessen, Aud (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"There is a widely held notion that death is not particularly visible in our culture; death is something we do not talk about. The premise for Døden i livet has been to challenge this preconception from a variety of perspectives and disciplines. The authors argue that death is present in our lives in many ways. We see it and experience it in our physical surroundings, for example in the various arrangements we make to remind ourselves of the dead. We hear or read about it in speeches, poems, music lyrics, psalms, obituaries, biographies, picture books, novels and newspapers. We talk about death in conversations with each other, in characterizing the dead and in clinical language about illness and death. We reveal our understanding of death through visual forms such as newspaper images, illustrations in books and in the imagery and metaphors we employ when we describe it. Døden i livet is a mult-disciplinary, scientific anthology consisting of 12 peer-reviewed chapters geared towards scholars and students interested in broader appreciation of how death is present in our culture. The chapters are written by researchers working in such diverse fields as health, pedagogics, idea history, religion, literature studies, linguistics and rhetoric."